PEMETAAN DAYA DUKUNG FONDASI DANGKAL DI WILAYAH UNIVERSITAS JEMBER BERBASIS CPT (CONE PENETRATION TEST) - Bagus Rahmat Hidayat; Paksitya Purnama Putra; Hernu Suyoso (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2020)
This research aims to make a bearing capacity distribution map of shallow foundations (footplate), which is to provide convenience in terms of examining substructure buildings planned by the consultant by the owner. Spatial concepts method, ArcGIS and kriging, are used to simplify the analysis stage in making bearing capacity maps. Bearing capacity distribution map of soil shows that most of the University of Jember area at two meters depth has hard soil consistency and has a bearing capacity of around 83.9 - 110.9 kg/cm2. The results of comparative analysis of ArcGIS and CPT has a ratio of 0,758 for point 1 and 0,765 for point 2.